1981
DOI: 10.1080/03014468100005171
|View full text |Cite
|
Sign up to set email alerts
|

Dizygotic twinning, marital stage and status and coital rates

Abstract: An attempt is made to isolate and quantify a positive correlation of parental coital rate with dizygotic twinning probability, by considering the variations of DZ twinning with marital stage and status. It is concluded that if the coital rate of young women is doubled, their DZ twinning probability is increased by a factor of very roughly 25-30%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…And-except in one important respect-these events may all be presumed to have promotional effects on coital rates, too. The exception is that the coital rates of young (under 20) unmarried (coitally active) women are substantially less than those of young married women [6]. Now in England and Wales, the DZ twinning rate of unmarried women aged less than 20 is lower than the comparable rate for married women [6].…”
Section: Jamesmentioning
confidence: 88%
“…And-except in one important respect-these events may all be presumed to have promotional effects on coital rates, too. The exception is that the coital rates of young (under 20) unmarried (coitally active) women are substantially less than those of young married women [6]. Now in England and Wales, the DZ twinning rate of unmarried women aged less than 20 is lower than the comparable rate for married women [6].…”
Section: Jamesmentioning
confidence: 88%
“…However, they are classified as unmarried. James (1981) , 1962-1966, and noted that the illegitimate DZ twinning rate is lower than the legitimate rate at the lowest maternal age (15-19) and is higher only at the higher maternal ages, resulting in a steeper slope. Also MacGillivray et al (1988) have observed a decreasing effect of marital status on the twinning rates.…”
Section: Statistical Inference Problems With Demographic Macrodatamentioning
confidence: 99%
“…A variety of factors have been associated with dizygotic twinning. These factors include advanced maternal age, parity, increased maternal height and weight, use of fertility drugs and contraceptives, social class membership, birth order, specific blood group characteristics, conceptions occurring after periods of sexual abstinence, and available nutritional supply (Nylander, 1975;Corney, Seedburgh, Thompson, Campbell, MacGillivray, & Timlin, 1981;Clark & Martin, 1982;Wyshak, Honeyman, Flannery, & Beck, 1983;James, 1983;Garza-Chapa, Escobar, Cerda, & Leal-Garza, 1984;Elwood, 1985). Ethnic differences in the DZ twinning rate have been associated with differences in many of these characteristics (Nylander, 1975).…”
Section: Factors Responsible For Twinningmentioning
confidence: 99%